Praktyczne wykorzystanie health literacy - alfabetyzmu zdrowotnego, jako narzędzia osiągania celów zdrowotnych = Practical use of health-literacy as a tool for achieving health goals - Dominik Olejniczak (Journal of Education, Health and Sport, 2016)
Olejniczak Dominik. Praktyczne wykorzystanie health literacy - alfabetyzmu zdrowotnego, jako narzędzia osiągania celów zdrowotnych = Practical use of health-literacy as a tool for achieving health goals. Journal of Education, Health and Sport. 2016;6(2):238-243. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.46654